2013
DOI: 10.1111/brv.12071
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion in ornithischian dinosaurs: an assessment using three‐dimensional computational modelling

Abstract: Ornithischian dinosaurs were primitively bipedal with forelimbs modified for grasping, but quadrupedalism evolved in the clade on at least three occasions independently. Outside of Ornithischia, quadrupedality from bipedal ancestors has only evolved on two other occasions, making this one of the rarest locomotory transitions in tetrapod evolutionary history. The osteological and myological changes associated with these transitions have only recently been documented, and the biomechanical consequences of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(109 citation statements)
references
References 144 publications
1
108
0
Order By: Relevance
“…3). Maidment et al (2014a) also found that the peak in femoral retractor moment arms occurred at more extended hip angles in quadrupedal ornithischians than in bipedal ornithischians (Fig. 4).…”
Section: Hind Limbmentioning
confidence: 66%
See 4 more Smart Citations
“…3). Maidment et al (2014a) also found that the peak in femoral retractor moment arms occurred at more extended hip angles in quadrupedal ornithischians than in bipedal ornithischians (Fig. 4).…”
Section: Hind Limbmentioning
confidence: 66%
“…2). PIFI functioned to protract and abduct the femur (Bates et al 2012), and elongation of the preacetabular process in all groups of quadrupedal ornithischian increased the moment arm of this muscle for femoral protraction (Maidment et al 2014a; Fig. 3).…”
Section: Hind Limbmentioning
confidence: 91%
See 3 more Smart Citations